Memory-associated immediate early genes: roles in synaptic function, memory processes, and neurological diseases - Khan, Zafar U.; Carretero-Rey, Marta; Muñoz-de-León-López, Cristina; Navarro-Lobato, Irene (Springer, 2025)
The expression of immediate early genes (IEGs) in the brain is rapidly upregulated during learning or in response to an event. This upregulation often correlates with neuronal activity in interconnected brain regions that form circuits associated with memory processing and formation. IEGs function either as transcription factors regulating gene expression or as effector proteins primarily involved in synaptic activities. AP-1 is a dimer composed of members of the Fos, Jun, ATF, and Maf transcription factor families. Its composition is a critical determinant of the expression of specific gene sets. AP-1 regulates a broad range of genes and is activated by various stimuli, including stress, drugs, learning, and exposure to new events. Other IEG transcription factors, such as Zif268 (Egr-1) and Npas4, regulate the transcription of genes essential for structural and synaptic plasticity. Conversely, effector proteins like Homer1a, Arc (Arg3.1), BDNF, and Narp contribute to AMPA receptor trafficking, its internalization, and both Hebbian and non-Hebbian forms of synaptic plasticity. Both types of IEGs play a critical role in memory and synaptic plasticity. Alterations in their function are associated with cognitive dysfunction in aging, as well as various neurological and psychiatric diseases. This review provides an overview of the current understanding of both types of IEGs in the regulation of different forms of synaptic plasticity, their contributions to memory functions, and their roles in aging and brain diseases.
Keywords: Neurología; Memoria; Cerebro - Enfermedades; Immediate early genes; AP1; CFos; CJun; Npas4; Zif268 (Egr1); Homer1a; Arc (Arg3.1); BDNF; Narp; Memory; Synaptic plasticity; LTP and LTD; Aging and neurological diseases